Risk factors of mortality in septicemic extramural neonates: an experience from resource limited setting of central India - Meshram, Rajkumar Motiram; Kadu, Kalyani S (Paediatrica Indonesiana, 2024)
Background: Sepsis is responsible for 30-40% neonatal deaths which can be attributed to various maternal, neonatal and sociocultural risk factors. Objective: To recognize the clinical and laboratory risk factors of mortality in extramural neonatal sepsis. Material and methods: Prospective observational study was conducted for duration of one year on extramural neonates with suspected sepsis. Maternal, neonatal and sociocultural factors were analyzed. Results: Average duration of hospital stay was shorter in non-survival compared to survival neonates (p=0.01). On univariate analysis preterm (p<0.001), weight<2500gms (p=0.01), home delivery (p=0.004) by Traditional Birth Attendant (p=0.003) , unbooked mother (p=0.03), peripartum febrile illness (p=0.02) and Premature rupture of membrane > 18 hours were the significant risk factors of mortality. Those neonates admitted with lethargy (p=0.04), hypothermia (p=0.01), respiratory distress (p<0.001), convulsion (p<0.0001), Jaundice (p=0.006), Apgar score <5at 1minute (p=0.01) , prolonged CFT (P<0.001), previously hospitalized (p<0.001) ,required mechanical ventilation (p=0.01),had thrombocytopenia (p=0.02), positive CRP (P<0.001), hypoglycemia (p=0.04), oxygen saturation ?90% (p=0.04), abnormal CSF/chest radiograph finding (p=0.002) had significantly higher mortality. Delivery conducted by traditional birth attendant, neonates travelled more than 80km, prematurity, bottle feed, h/o previous hospitalization, h/o lethargy, hypothermia, convulsions, prolonged CFT and isolation of micro-organisim were the independent risk factors of mortality in extramural neonates with sepsis Conclusion: Delivery conducted by traditional birth attendant, neonates travelled more than 80km, prematurity, bottle feed, h/o previous hospitalization, h/o lethargy, hypothermia, convulsions, prolonged CFT and isolation of micro-organisim were the independent risk factors of mortality in extramural neonates with sepsis.